Impact of aortic regurgitation on long-term outcomes in heart failure with preserved ejection fraction. (3rd October 2022) - De Colle, C; Paolisso, P; Gallinoro, E; Bertolone, D T; Mileva, N; Fabbricatore, D; Valeriano, C; Mancusi, C; Collet, C; Vanderheyden, M; De Luca, N; Van Camp, G; et al.
Abstract: Background: Aortic Regurgitation (AR) may aggravate the clinical course in patients with heart failure and preserved ejection fraction (HFpEF) by increasing filling pressures and triggering LV remodelling. Objective: To assess AR's prevalence and long-term prognostic implications in patients with HFpEF. Methods: The study population consisted of 458 consecutive patients (age 77.5±9.2 y, 57.9% females) hospitalized with de novo or worsened HFpEF. Patients with more than moderate aortic and/or mitral valve disease were excluded. Data on cardiovascular death, HF re-hospitalization and their composite (MACE) were collected. Results: Out of 309 (67.5%) patients with any AR, 156 (34.0%) and 153 (33.5%) had mild-AR and moderate-AR, respectively. The remaining 149 (32.5%) individuals had no-AR. Patients with versus without AR were significantly older with larger LV and LA volumes and a higher prevalence of diastolic dysfunction (all p<0.05). During a median follow-up of 33±25 months, a total of 114 patients (24.9%) died from cardiovascular causes, 126 patients (27.5%) were re-hospitalized for HF, while 272 (59.4%) had the composite endpoint (MACE). In multivariable Cox regression analysis, any AR emerged as an only independent predictor of MACE (HR=1.90, 95% CI 1.26–2.87, p=0.002). Mild-AR and Moderate AR increased the risk of MACE by 77% and 92%, respectively, compared to the No-AR (Figure). Conclusions: In patients with HFpEF, mild-to-moderate AR is highly prevalent, and it seems to identify individuals with worse long-term outcomes. This suggests that even mild AR should be considered a high-risk prognostic marker in patients with HFpEF. Funding Acknowledgement: Type of funding sources: None.